Adult Monarch (Danaus plexippus) Abundance Is Higher in Burned Sites Than in Grazed Sites - Leone, Julia B.; Larson, Diane L.; Larson, Jennifer L.; Pennarola, Nora; Oberhauser, Karen (Frontiers in Ecology and Evolution, 2019)
Much of the remaining suitable habitat for monarchs (Danaus plexippus) in Minnesota is found in tallgrass prairies. We studied the association of adult monarch abundance with use of fire or grazing to manage prairies. Sites (n=20) ranged in size from 1 to 145 hectares and included land owned and managed by the Minnesota DNR, U.S. Fish and Wildlife Service, The Nature Conservancy, and private landowners. We measured Asclepias spp. (milkweeds, monarch host plants) and forb frequency in 0.5 x 2-m plots located along randomly-placed transects that were stratified to sample wet, mesic, and dry prairie types at each site. Adult butterfly surveys took place three times at each site during the summers of 2016 and 2017, using a standardized Pollard Walk (400 meters). Data were analyzed using mixed effects models. Monarchs were more abundant at sites managed with prescribed fire than with grazing. We found no difference in milkweed and forb frequency between burned and grazed prairies. There was no relationship between monarch abundance and the other predictor variables tested: milkweed frequency, site area, forb frequency, and percent prairie in a 1.5 km buffer area surrounding each site. Monarch abundance was lowest at grazed sites with high stocking rates. Our findings suggest that milkweed and forb frequency do not vary between burned and grazed sites, although we only considered land management practices for the 12 years before the study and the most recent burns occurred in 2014, two years prior to the start of our study. They also suggest that heavy grazing may have negative impacts on monarchs.